An evaluation of the utility of commercially available modelling and simulation tools, used in conjunction with each other, for improving logistics support to UK Ministry of Defence urgent operational requirements - Smith, Jeremy C. D. (Cranfield University Press, 2012)
The UK Ministry of Defence has invested heavily in acquiring equipment under Urgent Operational Requirement (UOR) procedures. These enable accelerated procurement to fill urgent capability gaps. However, the dominance of time over cost and performance has led to sub-optimal logistics support that has manifested itself in poor system availability, and in support arrangements that do not represent best value-for-money. This paper describes experiments for improving support to UORs, using a range of modelling and simulation tools. The results indicate that there is utility in using general purpose, costing, and inventory optimization tools, in conjunction with each other.
Enduring and Cost Effective Engineering Solutions for the 21st Century
Keywords: Urgent Operational Requirements; operational availability; value-for-money; logistics; support; simulation modelling